Comparative study between real data and theoretical results calculated by ARIMA model to predict and calculate C02 emissions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this article, we have predicted and calculated by a statistical process called ARIMA model C02 emissions in Algeria during the period from 1963 to 2019, the data used here is a time series of the evolution of pollution caused by emissions of CO2. Our approach is based on four essential steps; the first is the identification of the model, the estimation of the parameters, the validation step and finally the forecast of certain future values. in Algeria from 1963 to 2019. Generall y this can be done through four essential steps, the first is the identification of the model, the estimation of the parameters, thevalidation step and finally the forecast of certain future values. The R software enables us exploit the theoretical results. It is found that ARIMA(1, 1, 2) model appears suitable for predicting future values of CO2 emissions.